Exploring lived experiences of female students on intimate partner violence at an institution of higher learning - Ndou, Nokuthula (My University, 2025)
Intimate Partner Violence (IPV) as a form of Gender Based Violence (GBV) is considered a societal problem and it occurs in all settings where there is an intimate relationship. IPV is global concern and Higher Education Institutions (HEIs) are also affected by this problem including South Africa. Researchers have previously studied IPV but there is still lack of studies on female students’ experiences with IPV at HEIs that were conducted in Limpopo, hence the study was conducted at an institution of higher learning in Limpopo. The study took the form of a phenomenological study aided with exploratory research objectives located within the qualitative paradigm. A total of eight female students from an institution of higher learning were interviewed. Participants were selected based on the fact that they have experienced IPV. The researcher made use of an interview guide and employed semi-structured face-to-face interviews using open-ended questions as a guide and as a data collection method. Data was analysed through deductive thematic content analysis. The findings of the study were centred on the experiences of participants and the role and function of the Gender desk, which highlighted the significance of reporting instances of IPV to the appropriate authorities as a crucial approach in tackling this problem. The findings in the study revealed that participants had experienced a diverse range of IPV such as emotional, sexual and sexual violence in the hands of their intimate partners. The participants were expected to possess knowledge of both the gender desk and the fundamental protocols for reporting cases of intimate partner violence. In addition, the findings discussed the subject of comprehending the protocols for reporting occurrences of IPV. Lastly, the findings focused on the intervention platforms implemented within the institution to tackle the problem of intimate relationship abuse. IPV has a substantial negative impact on the academic achievement of its victims due to the stress and trauma they experience.
Thesis (M. (Social Work)) -- University of Limpopo, 2025
Keywords: Gender based violence; Gender desk; Intimate partner violence; Higher education institution; Gender-based violence; Intimate partner violence; Universities and colleges